Efektivitas Penerapan Kebijakan Hukum Lingkungan Dalam Pengendalian Pencemaran Air Sungai Di Kawasan Ngoro Industrial Park (NIP) Kabupaten Mojokerto - Ika Rahmah Madaniyah; Annisa Alya Nurrizqi; Cholidah (Jurnal Hukum Saraswati, 2025)
River water pollution because of industrial activities inside the Ngoro industrial Park (NIP), Mojokerto, has come to be a serious environmental problem that requires powerful implementation of environmental law regulations. this newsletter targets to research the utility and effectiveness of environmental regulation rules (local law No. five/2023, government regulation No. 22/2021, and different associated regulations) in controlling water pollution at NIP, become aware of implementation obstacles, and examine the enforcement of environmental law at the studies place. using an normative juridical approach, this research well-knownshows that no matter existing policies, their implementation has now not been fully effective due to susceptible law enforcement, inadequate supervision, and coffee public participation. The findings suggest that modern environmental law enforcement mechanisms are insufficient to cope with the scale of pollution from industries including paper production, ice cream manufacturing, and rubber processing. The assessment indicates large gaps between prison norms and discipline implementation, with elements including restrained personnel, weak sanctions, conflicts of hobby, and occasional enterprise actor attention contributing to useless policy implementation. therefore, strengthening environmental law enforcement is wanted thru stepped forward supervision, more desirable administrative and crook sanctions, multiplied transparency and public participation, and higher coordination amongst stakeholders